Changes in Sleep Disruption in the Treatment of Co-Occurring Posttraumatic Stress Disorder and Substance Use Disorders - McHugh, R. Kathryn (2014)
Sleep disruption appears not only to reflect a symptom of posttraumatic stress disorder (PTSD), but also a unique vulnerability for its development and maintenance. Studies examining the impact of psychosocial treatments for PTSD on sleep symptoms are few and no studies to date of which we are aware have examined this question in samples with co-occurring substance use disorders. The current study is a secondary analysis of a large clinical trial comparing 2 psychological treatments for co-occurring PTSD and substance use disorders. Women (N = 353) completed measures of PTSD at baseline, end of treatment, and 3-, 6-, and 12-month follow-ups. Results indicated that the prevalence of insomnia, but not nightmares, decreased during treatment, and that 63.8% of participants reported at least 1 clinical-level sleep symptom at the end of treatment. Improvement in sleep symptoms during treatment was associated with better overall PTSD outcomes over time, χ(2)(1) = 33.81, p < .001. These results extend the existing literature to suggest that residual sleep disruption following PTSD treatment is common in women with co-occurring PTSD and substance use disorders. Research on the benefits of adding sleep-specific intervention for those with residual sleep disruption in this population may be a promising future direction.